2007
DOI: 10.1007/s11284-007-0376-x
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity compensates for low habitat quality and small patch size in the butterflyCupido minimus

Abstract: Habitat size, habitat isolation and habitat quality are regarded as the main determinants of butterfly occurrence in fragmented landscapes. To analyze the relationship between the occurrence of the butterfly Cupido minimus and these factors, patch occupancy of the immature stages in patches of its host plant Anthyllis vulneraria was studied in the nature reserve Hohe Wann in Bavaria (Germany). In 2001 and 2002, 82 A. vulneraria patches were surveyed for the presence of C. minimus larvae. The occurrence was lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…Similarly, in southeastern Sweden (Jonason et al 2010), butterfly species richness (not the abundance) was found to be positively related to increasing tree cover in the farm landscape. Apart from land use and farm management methods or farming practices (Weibull and Östman 2003), vegetation structure, quality of the matrix surrounding an agricultural habitat (Binzenhöfer et al 2008;Summerville et al 2008), diversity and types of habitats (Dessuy and de Morris 2007;Ngai et al 2008;Kumar et al 2009), landscape heterogeneity and habitat connectivity (Davis et al 2007) are important factors determining occurrence, movements, population dynamics, seasonality, persistence and longterm survival of Lepidoptera faunal communities in the agricultural landscapes (Dennis 2003;Greza et al 2004;Chay-Hernández et al 2006;Kivinen et al 2008;Öckinger and Smith 2008;Pickens and Root 2008;Stasek et al 2008;Dover and Settele 2009;Brückmann et al 2010). Generally, agricultural matrices that are more resembling a nearby forest patch maintain higher butterfly diversity than matrices with lesser shade cover (Summerville et al 2001;Kitahara and Watanabe 2003;Weibull and Östman 2003;Boriani et al 2005;Aviron et al 2007;Ohwaki et al 2007Ohwaki et al , 2008Barlow et al 2008;Bergman et al 2008;van Halder et al 2008;Marín et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in southeastern Sweden (Jonason et al 2010), butterfly species richness (not the abundance) was found to be positively related to increasing tree cover in the farm landscape. Apart from land use and farm management methods or farming practices (Weibull and Östman 2003), vegetation structure, quality of the matrix surrounding an agricultural habitat (Binzenhöfer et al 2008;Summerville et al 2008), diversity and types of habitats (Dessuy and de Morris 2007;Ngai et al 2008;Kumar et al 2009), landscape heterogeneity and habitat connectivity (Davis et al 2007) are important factors determining occurrence, movements, population dynamics, seasonality, persistence and longterm survival of Lepidoptera faunal communities in the agricultural landscapes (Dennis 2003;Greza et al 2004;Chay-Hernández et al 2006;Kivinen et al 2008;Öckinger and Smith 2008;Pickens and Root 2008;Stasek et al 2008;Dover and Settele 2009;Brückmann et al 2010). Generally, agricultural matrices that are more resembling a nearby forest patch maintain higher butterfly diversity than matrices with lesser shade cover (Summerville et al 2001;Kitahara and Watanabe 2003;Weibull and Östman 2003;Boriani et al 2005;Aviron et al 2007;Ohwaki et al 2007Ohwaki et al , 2008Barlow et al 2008;Bergman et al 2008;van Halder et al 2008;Marín et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This does not mean, however, that host and nectar plants are unimportant as they are the prerequisites for successful reproduction, and have been identified as important determinants of patch occupancy in butterflies (Dennis & Eales, 1997;Thomas et al, 2001;Wahlberg et al, 2002;Krauss et al, 2004Krauss et al, , 2005Binzenhöfer et al, 2007;Grundel & Pavlovic, 2007). Indeed, in this study the host plant number correlated significantly with patch area, although there was large variation in average plant number (see also Krauss et al, 2005;Grundel & Pavlovic, 2007;Rabasa et al, 2007).…”
Section: Influence Of Host and Nectar Plantsmentioning
confidence: 60%
“…Chequered blue occupies exposed bedrock areas, which are likely to be less affected by within patch succession, compared with clearcuts, grassland or meadows (Wahlberg et al, 2002;Krauss et al, 2005;Binzenhöfer et al, 2007). However, the host plant dynamics is likely to be very important for short-term butterfly dynamics, compared with the successional dynamics of the patches themselves and their immediate surroundings.…”
Section: Influence Of Host and Nectar Plantsmentioning
confidence: 99%
“…Strong effect of connectivity on site occupancy patterns is often assumed to indicate a metapopulation dynamics, in which local extinctions are compensated by recolonisation processes (Hanski 1999). Existence of such effect on site occupancy of another small-sized lycaenid, Cupido minimus (Fuessly, 1775) was interpreted in terms of the species' dispersal ability (Binzenhofer et al 2008;Krauss et al 2004). In our case, the absence of effect on P. thersites might be interpreted in two ways.…”
Section: Discussionmentioning
confidence: 99%